A combined in vitro approach to improve the prediction of mitochondrial toxicants. (August 2016) - Eakins, Julie; Bauch, Caroline; Woodhouse, Heather; Park, Benjamin; Bevan, Samantha; Dilworth, Clive; Walker, Paul
Abstract: Drug induced mitochondrial dysfunction has been implicated in organ toxicity and the withdrawal of drugs or black box warnings limiting their use. The development of highly specific and sensitive in vitro assays in early drug development would assist in detecting compounds which affect mitochondrial function. Here we report the combination of two in vitro assays for the detection of drug induced mitochondrial toxicity. The first assay measures cytotoxicity after 24 h incubation of test compound in either glucose or galactose conditioned media (Glu/Gal assay). Compounds with a greater than 3-fold toxicity in galactose media compared to glucose media imply mitochondrial toxicity. The second assay measures mitochondrial respiration, glycolysis and a reserve capacity with mechanistic responses observed within one hour following exposure to test compound. In order to assess these assays a total of 72 known drugs and chemicals were used. Dose–response data was normalised to 100 × Cmax giving a specificity, sensitivity and accuracy of 100%, 81% and 92% respectively for this combined approach. Highlights: Assessment of two in vitro assays to detect mitochondrial toxicity in HepG2 cells. Measurement of mitochondrial respiration, glycolysis and reserve capacity by XF e 96. Potential mechanism of mitochondrial toxicity can be predicted using the extracellular flux assay. Combining Glu/Gal and extracellular flux assays improves predictivity of mitochondrial toxicants.